Hybridity and the New African Diaspora: A Feminist Reading of Chimamanda Ngozi Adichie’s Americanah - DJAFRI ,Katiba; CHERAIFIA, Djihed (Faculty of Letters and Foreign Languages Department of English, 2025)
With the rise of globalization, African migration to the West has produced a new type of diaspora, the New African Diaspora. While deeply rooted in economic pursuit or political reasons, the New African Diasporic narratives navigate new perspectives that focus on the individual migration experience that is characterized by the exploration of the self, hybrid identity formation, assimilation challenges, and personal ambitions. Chimamanda Ngozi Adichie, a Nigerian author, captures the complexities of the migration experience within the context of globalization, gender, and the new African diaspora in her novel Americanah. In Americanah, Adichie challenges conventional African diasporic narratives by positioning love as a central motive for migration. At the same time, she explores how Globalization, gender, and pressures of integration shape both male and female migrant experiences and identity formation. This dissertation explores the intersection of globalization, postcolonialism, and feminism by conducting an interdisciplinary study of Americanah. It aims to understand how gender influences the female and male migration experience in the West and investigate how globalization, and the struggle between cultural preservation and assimilation shape hybrid identities among African migrants in Americanah. Through literary analysis, the dissertation concludes that identity in the age of globalization is fluid, hybrid, and deeply influenced by gender and assimilation pressures. The dissertation contributes to feminist diaspora studies and deepens the understanding of African literature in a globalized context.